Relations Between Instructional Practices and On-Task Behavior in Classrooms Serving American Indian Students. Issue 2 (3rd April 2017) - McComas, Jennifer J.; Downwind, Ida; Klingbeil, David A.; Petersen-Brown, Shawna; Davidson, Katherine M.; Parker, David C.
ABSTRACT: Achievement disparities between American Indian students and non-American Indian peers are persistent and well documented. Student engagement is a promising target for intervention given its relation to academic achievement. This study investigated the relation between specific teacher practices (opportunities to respond [OTRs], praise, and reprimands) and classroom on-task behavior in an urban, public K–8 school that serves primarily American Indian students. OTRs and praise were positively associated with student on-task behavior, whereas reprimands were negatively associated with on-task behavior. Results from multilevel logistic regression indicated that OTRs significantly increased the likelihood that a classroom was highly on-task, whereas the reprimands significantly decreased the likelihood. Praise did not have a significant effect after controlling for the other variables in the model. Results are interpreted in a context of evidence-based instructional practices for increasing OTRs and praise, decreasing reprimands, and ultimately enhancing on-task behavior in an urban classrooms serving primarily American Indian youth.